Education in Senior and Vocational Schools in Tangerang City: Educational Planning Approaches, Stakeholder Engagement, and Suitability of Education Policies with School Needs: Education in Senior and Vocational Schools in Tangerang City: Educational Planning Approaches, Stakeholder Engagement, and Suitability of Education Policies with School Needs - Baghas Budi Wicaksono; Heri Satrianto; Rinintha Parameswari (LPPM Universitas Buddhi Dharma, 2026)
This study aims to identify the effect of educational resources, stakeholder engagement, and education policy alignment on the educational planning of Senior High Schools and Vocational High Schools in Tangerang City. “Educational resources and stakeholder engagement play vital roles in ensuring that schools provide quality learning environments, while the alignment between education policies and school needs remains crucial for effective educational planning. This study employs a quantitative research method.”. “The results show that the t-statistic for educational resources (8.453 > 1.985; p = 0.000 < 0.05) indicates a positive and significant effect on educational planning. The t-statistic for stakeholder engagement is 6.568 > t-table 1.985 with a significance value of 0.000 < 0.05, also indicating a positive and significant effect on educational planning. Furthermore, the F-statistic of 153.927 > F-table 4.09 with a significance value of 0.000 < 0.05 shows that educational resources, stakeholder engagement, and policy alignment collectively have a significant and positive impact on the educational planning of Senior High Schools and Vocational High Schools in Tangerang City.